Analysis of The Concept of Women's Careers According to Feminism as Well as Contradictions in The Islamic Perspective - Puspita, Erva Dewi Arqomi; Paidiah, Rizkiatul; Marlia, Ana Dwi; Fadillah, Putri (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: The development of feminism issues over time has led to this ideology increasingly dominating the views of women in various aspects of life. The doctrine of radical feminism has shaped the social view of women reviewed from a capitalist perspective, achievement, and work ethos. The historical events of the 1970s were full of discrimination against women by church culture, which sparked a rebellion for equal rights with men. It builds a paradigm that women must have achievements and social influence to gain societal rights and capacity. Therefore, a career becomes the main aspiration of feminism. However, this affects the shift in the roles and responsibilities of women traditionally identified as wives and mothers and responsible for the household. For feminism, being a career woman is the right of all women, and not limited to domestic roles. The study examines the contradiction between feminism and Islamic perspectives on women's careers. The method used is qualitative research based on library research, with descriptive analysis and critical analysis approaches. The results of this study reveal that the concept of women's careers according to feminism is based only on the trauma of the church's cultural history that intimidates women. But Islam is based on the good and the glory of women.